STUDENTS’ PERCEPTION OF LEARNING MANAGEMENT SYSTEM ON STUDENTS’ STUDY HABIT DURING COVID-19 - Balogun, Naeem Atanda; Isimikalu , Mary I.; Adedoyin, Adeyinka (FUDMA JOURNAL OF SCIENCES, 2022)
The study investigated perception of students on Learning Management System and how it affects and benefits their study habit during COVID-19, as well as its effects on their study performance. The study adopted quantitative research approach and survey design where data was gathered using a questionnaire that was created to acquire pertinent information from respondents. The study participants are the 200 and 300 level students of Faculty of Education, University of Ilorin, while a total of 358 students administered the questionnaire only 303 responses are used for the study. The results demonstrated that students’ study habits are significantly impacted by the use of Learning Management Systems (LMS) as majority of the respondents attest that the use of LMS improved their study habit which in turn affected their study result positively. These could also assist lecturers and university administration to know how well students are able to relate with Learning Management System, how it affects their academic performance and their preparedness to fully adopt the system.